مهارات ما وراء المعرفة كمتنبئات بالتكيف الأكاديمي لدى طلاب السنة الأولى بجامعة الملك سعود - Boraik, El-sayed (Jordan Journal of Educational Sciences, 2019)
The current study aimed at identifying the level of the metacognitive skills and the academic adjustment of the first year students at King Saud University, in addition to the role of the metacognitive skills as the predictor of academic adaptation. The study sample consisted of (200) students; (104) students from the scientific colleges track, and (96) students from the humanities colleges. The scale of metacognitive skills and the academic adjustment scale (preparation / researcher) were applied. The study concluded that: there are no statistically significant differences between the means of the metacognitive skills and academic adjustment of students in the first year of King Saud University according to the variable of specialization (scientific – humanities). Also, there is a positive statistically significant correlation between the metacognitive skills and the academic adjustment of the first year students at King Saud University. Moreover, there is a linear relationship between the metacognitive skills and academic adjustment, and the metacognitive skills explain (22%) of the variance in the academic adjustment of the first year of King Saud University students